The Relationship between Job Stress and Employee Job Satisfaction : A Multivariate Analisis Approach in an Organizational Context - Nanda Hidayati; Chaeranti Muldayani Dewi; Esti Handayani; Dana Budiman; Hartati Maango (West Science Business and Management, 2023)
Significant interest and study have been focused on the connection between job stress and employee job satisfaction in organizational psychology. This study uses a multivariate analysis technique to examine the association between workplace stress and job satisfaction among Gen Z workers in Bandung, Indonesia. A cross-sectional survey of Gen Z employees from various firms in Bandung is used as part of the study's quantitative research design. Data will be gathered using a standardized questionnaire that evaluates job stress, job satisfaction, and potential moderating factors within the organizational context. The collected data will be examined using descriptive statistics, reliability analysis, and multivariate analytic techniques such multiple regression analysis, mediation analysis, and moderation analysis. The research's results and conclusions will advance our understanding of organizational management and employee well-being while shedding light on the relationship between Gen Z workers' job satisfaction and workplace stress. The study's ramifications will be examined, along with suggestions for how businesses may better control employee stress and boost job happiness among Bandung's Gen Z workforce.